ANALISIS VALUASI SAHAM SYARIAH SEKTOR BATUBARA MENGGUNAKAN METODE FCFE DAN RELATIVE VALUATION DIMASA PANDEMI COVID-19 YANG TERDAFTAR DI ISSI - Rusdi Riduan Pulungan; Maryam Batubara; Nur Ahmadi Bi Rahmani (Jurnal Akuntansi dan Pajak, 2023)
In stock investing, various market sentiments, both negative and positive, come one after another to make the performance of stocks fluctuate more regardless of their own fundamental factors, both in crisis situations and in conducive market conditions it is very important for investors to know the intrinsic value of a stock in order to make the right decision in choosing stocks, and make decisions when to buy, hold or sell. This study aims to determine the intriguing value of coal sector stocks listed on the Indonesian Sharia Stock Index (ISSI) using the FCFE and Relative Valuation methods. This research uses fundamental analysis methods with a quantitative descriptive approach. The results of this study are known that the calculation results of the FCFE method when compared to the price on December 31, 2021, HRUM shares are still Undervalued at Rp. 12,389. Furthermore, the shares are still undervalued at Rp. 55,112. Then BOSS shares are still undervalued at Rp. 102. Then the calculation results using the Relative Valuation method are calculated with the P/E Ratio of HRUM shares already Overvalued Rp. 846. Furthermore, BSSR shares are still undervalued at Rp. 12,748. Finally, BOSS shares have been overvalued at Rp.-1,349 or Rp. 50. When calculated by PBV (price to Book Value) HRUM shares of Rp. 1,928 are overvalued, then BSSR shares of Rp. 3,918 are overvalued, and BOSS shares of Rp. -157 or Rp. 50 are overvalued.